South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper estimates an equilibrium path for South Africa's real effective exchange rate. The paper briefly describes the dynamics of the real exchange rate and its determinants. It investigates the presence of a long-term relationship between the real exchange rate and certain explanatory variables, estimates the speed at which the real exchange rate converges toward its equilibrium level, and derives measures for the equilibrium real exchange rate. The paper also examines the real money demand, consumer prices, and the real exchange rate in South Africa.